An accelerated physical sulfate attack test using an induction period and heat drying: First applications to concrete with different binders including ground glass pozzolan and limestone filler. (22nd August 2022) - Esselami, Redha; Wilson, William; Tagnit-Hamou, Arezki
Graphical abstract: Highlights: Heat drying, and induction techniques accelerated physical sulfate attack mechanism. Ground glass pozzolan is more efficient in mitigating physical sulfate attack on concrete compared to limestone filler. High sulfate resistance cement type is prone to physical sulfate attack similarly to general use Portland cement. The developed accelerated PSA test protocol generated results after 15 cycles of exposure during 30 days. Concrete scaling occurred mostly during cold-wet cycle when formation of mirabilite crystals is triggered. Abstract: This study aims to investigate an accelerated protocol to test physical sulfate attack on concrete with different types of binders. To speed up the accumulation of sodium sulfate within the binder matrix and the initiation of the mirabilite-thenardite phase transition, the proposed protocol consists of heat drying specimens before and after 15 days of immersion in a concentrated sodium sulfate solution. After this preconditioning, the partial immersion mode under dry-wet cycling regimes was found to result in higher visual damage compared to the full-immersion mode. For similar water absorption rates, concrete prepared with general use cement and high sulfate resisting cement showed similar deterioration rates despite their different tricalcium aluminate contents. Partial replacement of cement with 20% ground glass pozzolan delayed concrete damage contrary to the replacement with 10% limestone which resulted in faster physical sulfate attack.